Qualidade e conservação pós-colheita de melão cantaloupe ‘hy mark’ sob diferentes fontes de nitrogênio e adubação potássica - Sousa, Francisco de Assys Romero da Mota (2016)
The melon productivity (Cucumis melo L.) is very variable among the producers and, in most cases, lower than their productive potential. The present research aims to evaluate the influence of different doses of N and K on the quality and sensorial acceptance of Cantaloupe 'Hy Mark' melon cultivated in the Brejo region of Paraiba, determining the ones that are most suitable for commercial scale. The melons were cultivated in the experimental unit called the Chã de Jardim and a DBC in 3 blocks with 10 subdivided plots in the Campus II Agrarian Sciences Center, Areia, PB, where they were harvested at the appropriate point. (L *, a *, b *), fruit length and diameter, firmness, pH, soluble solids, titratable acidity, SS ratio / AT, total sugars, reducing and non - reducing, total extractable polyphenols, total antioxidant activity by ABTS radical capture, carotenoids, flavonoids, anthocyanins and sensory analysis. 228 kg ha-1 of Nitrogen and 252 kg K2O ha-1 of Potassium is the dose that provides fruits with quality to the Markt. Nitrogen has a direct influence on the antioxidant activity of melon. Potassium is the nutrient that provides the melon with the higher values for the physical and physical-chemical variables, contributing to the quality of the product.